From mainstream to revolution Franciscan activities in the Diocese of Nueva Caceres, Kabikolan, 1768-1898 - Totanes, Stephen Henry S. (2007)
This paper serves as a sequel to an earlier research project on Franciscan missions evolving into mainstream parishes in Kabikolan from 1578-1768. By 1768, the Franciscans were already administering the majority of the parishes in the Diocese of Nueva Caceres which had jurisdiction over the provinces of Ambos Camarines and Albay in Kabikolan and portions of Tayabas (now Quezon) province in southern Luzon. In this year, the Franciscans expanded their evangelical work to the island of Samar with the expulsion of the Jesuits from the Philippines, who turned over some of their parishes in Eastern Visayas to the Franciscans upon their departure. For the next one hundred and thirty years, the Franciscans continued to maintain their presence in Kabikolan, albeit, in many instances, competing with and eventually yielding some of these parishes in their jurisdiction to the secular clergy. This period also coincided with the establishment of the twenty-one California missions under the leadership of Fray Junipero Serra, O.F.M., across the Pacific Ocean, along the western coast of the North American continent. With the establishment of the Seminario Conciliar de Nueva Caceres in the late 18th century and the training of native secular priests being sponsored by the Diocese, more and more Bikolanos were taking on the helm of the parishes in their region and replacing the Franciscan friars. At the outbreak of the Revolution in the Tagalog region in 1896, nearly half of the parishes in Kabikolan were already in the hands of the native secular clergy. But in the crackdown that followed the discovery of the Katipunan, three native Bikolano priests were among those in a group executed in Bagumbayan on January 4, 1897 that came to be known in Bikol history as the ?Quince Martires.? The Franciscans would bear the brunt of the repercussions of these executions the following year, when a revolt led by officers of the local Guardia Civil in September 1898 resulted in the imprisonment of twenty-two Franciscan friars in their own convent and church in San Francisco, in the center of the town of Nueva Caceres, and their eventual abandonment of most of their parishes in Kabikolan.